ANALISIS PERBANDINGAN RASIO KEUANGAN PEMERINTAH PROPINSI DI PULAU JAWA - Arthaingan H. Mutiha (Fakultas Ekonomi, Universitas Negeri Jakarta, 2018)
The purpose of this study is to analyze the comparison of provincial governmentfinancial performance in Java and to find out whether there are differences in financial performance among provincial governments. The data used in this study is secondary data for five provinces in Java Island namely Banten, West Java, Central Java, DI Yogyakarta and East Java. The data used is for the period of 2013 until 2016 and data is taken from the Central Bureau of Statistics. The financial performance indicators used in this study are financial ratios such as Decentralization Degree Ratios, Regional Financial Independence Ratios and Expenditure Harmonization Ratios. The results of this study indicate that the best average financial performance is East Java (1,12) then followed by Central Java (0,96), Banten (0,92), West Java (0,90) and DI Yogyakarta (0,59) Meanwhile, different test results of Kolmogorov Smirnov test showed that there is no significant difference between the financial performance of five provinces in Java. Keywords :Decentralization Degree Ratios, Regional Financial Independence Ratios andExpenditure Harmonization Ratios, Financial Ratio